Cognitive, emotional and inferential paths from price perception to buying intention in an integrated brand price image model - Stephan Zielke; Deonir De Toni; José Afonso Mazzon (SN Business & Economics, 2022)
A brand price image consists of associations related to the price positioning of a brand's product portfolio and has a filter function for price search and brand consideration. The branding literature usually analyzes brand images in general and a few studies have discussed variables related to dimensions of a brand price image. This paper aims to extend this fragmented literature by proposing an integrated framework that links cognitive, emotional and inferential dimensions of a brand price image with each other and with the buying intention. With this framework, we analyze how brand price-level perception influences the buying intention through different positive and negative paths and whether the strength of these paths differs between price tiers. We test our framework based on data from 581 young middle-class Brazilian respondents using structural equation modeling. Results reveal a negative net effect of a perceived low price level on the buying intention. Regarding intra-tier positioning, a more expensive price-level perception increases the buying intention in low price tiers, while a less expensive price-level perception has a positive effect in high-price tiers. We explain these effects by stronger price–quality inferences in low-price tiers and discuss implications for theory and practice.
Keywords: M31; 330; Brands; Inference; Price image; Price level; Price tier